Stem Cell Therapy in Chronic Periodontitis: Host Limitations and Strategies - Zhang, Zhiyu; Deng, Mengting; Hao, Meng; Tang, Jianxia (Frontiers in Dental Medicine, 2022)
The treatment of chronic periodontitis is undergoing a transition from simple plaque removal and replacement with substitute materials to regenerative therapy, in which stem cells play an important role. Although stem cell-based periodontal reconstruction has been widely explored, few clinical regeneration studies have been reported. The inflammatory lesions under the impact of host factors such as local microbial–host responses, may impede the regenerative properties of stem cells and destroy their living microenvironment. Furthermore, systemic diseases, in particular diabetes mellitus, synergistically shape the disordered host-bacterial responses and exacerbate the dysfunction of resident periodontal ligament stem cells (PDLSCs), which ultimately restrain the capacity of mesenchymal stromal cells (MSCs) to repair the damaged periodontal tissue. Accordingly, precise regulation of an instructive niche has become a promising approach to facilitate stem cell-based therapeutics for ameliorating periodontitis and for periodontal tissue regeneration. This review describes host limitations and coping strategies that influence resident or transplanted stem cell-mediated periodontal regeneration, such as the management of local microbial–host responses and rejuvenation of endogenous PDLSCs. More importantly, we recommend that active treatments for systemic diseases would also assist in recovering the limited stem cell function on the basis of amelioration of the inflammatory periodontal microenvironment.